Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai - Faris, Faris Fadhilah; Budiasih, Yanti (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
ABSTRACTThis research aims to examine and analyze the influence of the work environment and work motivation on the performance of employees at the Archives Center of the National Research and Innovation Agency (BRIN) Gunung Sindur. The total population in this study was 50 employees at the Finance Bureau and BMN of the General Election Supervisory Agency of the Republic of Indonesia.            The data collection method in this research was carried out by distributing questionnaires to 50 employee respondents at the Central Archives office of the National Research and Innovation Agency (BRIN) Gunung Sindur. The research method used is a quantitative method that is associative in nature using primary data.            These results indicate that the Work Environment has a positive and significant effect on employee performance with a calculated t value greater than t table 4.605 2.01 and a significant value of 0.000 0.05, Work Motivation has a positive and significant effect on employee performance with a t value count more. The size of the t table is 3.316 2.01 and the significant value is 0.002 0.05. Together the Work Environment and Work Motivation have a positive and significant effect on employee performance with a calculated F value greater than F table 1118.979 3.20 and a significant value of 0.000 0.05. Keywords : Employee Performance, Work Environment and Work Motivation.